HUBUNGAN CITA RASA DAN SISA MAKANAN LUNAK PASIEN KELAS III DI RSUD BERKAH KABUPATEN PANDEGLANG - Anggraeni, Diah; Ronitawati, Putri; Hartati, Lilik Sri (Jurnal Nutrire Diaita (Ilmu Gizi), 2017)
Abstract The leftover is a classic problem founded in many hospitals in Indonesia. The number of leftover can cause loss of nutrition for patient after hospitalization. Lack of nutrients will have an impact on nonoptimal nutritional status which will disrupted the healing process. If the patient does not finish the food as well as recommended and this goes on for a long time, it will cause the nutrients deficiency, also resulting in hospital malnutrition. The fact in supplying the soft-food for patient, there were number of foods left since patient whose supplied by soft-food has a serious condition than the normal food patient. The high level of water in soft food causing the high volume of food and must contained by non-stimulated seasoning. This research aimed to determine the correlation between the taste of soft-food for patient in Berkah Hospital Pandeglang, especially for patient at level 3 facility. This research took a sample of level 3 patients, because this class has the largest bed capacity is in the hospital. This study is descriptive analytic, with cross sectional design, and the sample amounted to 70 people. Interview conducted by questionnaire then the direct weighing process for soft-food leftover held for 2 days. Analysis process used the chi square test. The result of bivariate analysis with chi square test was obtained by the taste of breakfast menu (p Value = 0,017), lunch (p Value = 0,008) and dinner (p Value = 0,009). The results showed there was a relationship between the taste and the soft-food leftover for breakfast (p <0.05), afternoon (p <0.05), and night (p <0.05). It recommended to held an periodically evaluation for the menu (in 6 months), especially on the taste of food aspect, especially if the food remains more and more. Keywords : leftover, taste of food, soft food, nutrition